Strengthening Teacher Competence in the Harapan Bunda Semarang Learning Community through E-Comics Based Learning: Penguatan Kompetensi Guru di Komunitas Belajar Harapan Bunda, Semarang melalui Pembelajaran Berbasis E-Comic - mochamad abdul basir; Amin Suyitno; Mohamad Aminudin; Hevy Risqi Maharani (Altifani Journal: International Journal of Community Engagement, 2025)
Community service activities aim to strengthen teacher competency through training and mentoring in making E-Comic s and their digital assessments to improve student learning outcomes. The training participants were 18 teachers who are members of the Harapan Bunda learning community, Semarang. The integrated E-Comic-making problem-solving training with digital assessments was carried out through a group-based, comprehensive, and human resource-based approach. Furthermore, the three methods were implemented in four stages, namely (a) socialization; (b) competency improvement; (c) action mentoring, and (d) monitoring and evaluation. The training was conducted for one month with two offline meetings and the rest was mentored online. After being given training in making E-Comic s and digital assessments through Live worksheets, it showed that there was an increase in teacher understanding of the material for making E-Comic s by 71%, there was an increase in teacher understanding in utilizing technology to create interactive and interesting learning materials by 53%. Teachers were also able to integrate E-Comic s and live worksheets with digital assessments to develop a more comprehensive learning experience by 88%. It is recommended that training participants integrate E-Comic creation and digital assessment with the curriculum to ensure that the use of these technologies remains relevant and supports learning objectives.